A Cyclist-Domain-Based Method for Evaluating the Level of Service of a Bicycle Lane. (8th June 2020) - Zhang, Sheng; Liang, Jun; Huang, Zhongxiang
Abstract : Evaluating the level of service (LOS) of bicycle lanes is essential in planning, designing, and maintaining bicycle infrastructure. This study presents a new concept—the cyclist domain—for characterizing interactions between cyclists and proposes a cyclist-domain-based method for evaluating the LOS of bicycle lanes. Unlike conventional bicycle lane LOS evaluation method, which counts the weighted events numbers and may generate inaccurate results and even misleading decisions, we specified four types of overlapping cyclist domains to characterize potential impacts in various riding events. The cyclist domain influence ratio (CDIR) derived from cycling trajectories is used to measure the negative impact between cyclists. We then propose an LOS evaluation method for bicycle lanes based on CDIRs. The user comfort is defined as the sum of products of CDIRs and respective durations. The bicycle lane LOS is then evaluated by the average comfort of all users. The case study shows that the proposed method can efficiently and effectively evaluate the bicycle lane LOS.